Compact microwave kinetic inductance nanowire galvanometer for cryogenic detectors at 4.2 K. (14th February 2018) - Doerner, S; Kuzmin, A; Graf, K; Charaev, I; Wuensch, S; Siegel, M
Abstract: We present a compact current sensor based on a superconducting microwave lumped-element resonator with a nanowire kinetic inductor, operating at 4.2 K. The sensor is suitable for multiplexed readout in GHz range for large-format arrays of cryogenic detectors. The device consists of a lumped-element resonant circuit, fabricated from a single 4 nm-thick superconducting layer of niobium nitride. Thus, the fabrication and operation is significantly simplified in comparison to state-of-the-art current readout approaches. Because the resonant circuit is inductively coupled to the feed line the current to be measured can directly be injected without having the need of an impedance matching circuit, reducing the system complexity. With the proof-of-concept device we measured a current noise floor δI min of 10 pA/Hz 1/2 at 10 kHz. Furthermore, we demonstrate the ability of our sensor to amplify a pulsed response of a superconducting nanowire single-photon detector using a GHz-range carrier for effective frequency-division multiplexing.